Advanced Steganography Method for Digital Images Using Eight-sided Side Match - Mahdi Saleh, Salah (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this paper, we present an advanced steganography method by using the side information of the eight neighboring pixels. It aims to provide a secure steganography system and to minimize the distortion of the stego-image. The method exploits the correlation between neighboring pixels to estimate the degree of smoothness or contrast of pixels to determine the amount of payload in each embedding position. If the pixel is located in edge area, then it tolerates larger changes than those in smooth areas. The eight-sided side match method is used in our scheme. It attempts to share all the surrounded pixels in determining the capacity of each embedding position. The experimental results show that our method provides a high quality image without making noticeable distortion. Another important thing in our advanced method is that the embedded data can be extracted from the stego-image without referencing the original image. This means that the stego-image will depend on itself in extracting embedded information without using any external factor or key.